Examining the Effects of Customer Experience and Price Perception on Repurchase Intention: Evidence from Scarlett’s House Restaurant, Blok M - Silvy Geovanny Karjadi; Ika Suryono Djunaid (Darul Yasin Al Sys, 2026)
The increasingly competitive culinary industry in the Blok M area of South Jakarta requires restaurant managers to understand the factors that encourage customers not only to make initial visits but also to develop repurchase intentions. This study aims to examine the effect of customer experience and price perception on repurchase intention among customers of Scarlett’s House Blok M Restaurant. This study employed a quantitative approach using a non-probability sampling method with purposive sampling. The respondents comprised 100 customers who had previously visited Scarlett’s House Blok M. Data were collected through questionnaires and analyzed using PSPP. The findings indicate that customer experience has a significant effect on repurchase intention, as shown by a t-value of 2.09. Price perception also has a significant effect on repurchase intention, with a t-value of 4.59, indicating that customers’ assessment of price suitability plays an important role in shaping their intention to repurchase. The simultaneous test further demonstrates that customer experience and price perception collectively influence repurchase intention, with an F-value of 35.11. The multiple linear regression results show that both variables explain 41% of the variation in repurchase intention, while the remaining 59% is influenced by factors outside this study. This study concludes that improving customer experience and ensuring that prices are aligned with the perceived value received by customers can enhance repurchase intention at Scarlett’s House Blok M. The findings contribute to consumer behavior and restaurant marketing literature by confirming the importance of experiential and price-related factors in strengthening customer retention. Practically, the study provides recommendations for restaurant management to improve service quality, create memorable dining experiences, and maintain pricing strategies that are consistent with customer expectations.